No dose-dependent increase in fracture risk after long-term exposure to high doses of retinol or beta-carotene - Ambrosini, G.; Bremner, A.; Reid, Alison; Mackerras, D.; Alfonso, Helman; Olsen, N.; Musk, A.; De Klerk, N. (2013)
Summary: Uncertainty remains over whether or not high intakes of retinol or vitamin A consumed through food or supplements may increase fracture risk. This intervention study found no increase in fracture risk among 2,322 adults who took a controlled, high-dose retinol supplement (25,000 IU retinyl palmitate/day) for as long as 16 years. There was some evidence that beta-carotene supplementation decreased fracture risk in men. Introduction: There is conflicting epidemiological evidence regarding high intakes of dietary or supplemental retinol and an increased risk for bone fracture. We examined fracture risk in a study administering high doses of retinol and beta-carotene (BC) between 1990 and 2007. Methods: The Vitamin A Program was designed to test the efficacy of retinol and BC supplements in preventing malignancies in persons previously exposed to blue asbestos. Participants were initially randomised to 7.5 mg retinol equivalents (RE)/day as retinyl palmitate, 30 mg/day BC or 0.75 mg/day BC from 1990 to 1996; after which, all participants received 7.5 mg RE/day. Fractures were identified by questionnaire and hospital admission data up until 2006. Risk of any fracture or osteoporotic fracture according to cumulative dose of retinol and BC supplementation was examined using conditional logistic regression models adjusting for age, sex, smoking, body mass index, medication use and previous fracture. Results: Supplementation periods ranged from 1 to 16 years. Of the 2,322 (664 females and 1,658 males) participants, 187 experienced 237 fractures. No associations were observed between cumulative dose of retinol and risk for any fracture (OR per 10 g RE = 0.83; 95 % CI, 0.63-1.08) or osteoporotic fracture (OR per 10 g RE = 0.95; 95 % CI 0.64-1.40). Among men, cumulative dose of BC was associated with a slightly reduced risk of any fracture (OR per 10 g = 0.89; 95 % CI 0.81-0.98) and osteoporotic fracture (OR per 10 g = 0.84; 95 % CI 0.72-0.97). Conclusions: This study observed no increases in fracture risk after long-term supplementation with high doses of retinol and/or beta-carotene. © 2012 International Osteoporosis Foundation and National Osteoporosis Foundation.